Here's the question you clicked on:
sharron482
In solving the equation (x + 4)(x – 7) = -24, Eric stated that the solution would be x + 4 = -24 => x = -28 or (x – 7) = -24 => x = -17 However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning
If you have a*b=-24, this doesn't mean a=-24 or b=-24 of both=-24 Think of all the factors of -24. What is possible for a and b to be?